Pressure Drop Characteristics of Subcooled Water in a Hypervapotron under High and Non-Uniform Heat Fluxes - Ge Zhu; Ge Mei; Jianguo Yan; Shujian Tian (Energies, 2023)
To study the pressure drop characteristics of hypervapotron, which was designed as a water-cooling structure in the divertor dome of the fusion reactor, the pressure drop tests of subcooled water were carried out in a vertically upward hypervapotron. To simulate the one-side radiant heating condition in the engineering application, the non-uniform heat fluxes were obtained by using the off-center electrically heating method. The system parameters were as follows: mass flux G = 2000–5000 kg·m−2·s−1, inlet pressure p = 2–4 MPa, and equivalent one-side radiating heat flux qe = 0–5 MW·m−2. The effects of the parameters on the pressure drop were discussed in detail. It was observed that in the single-phase (SP) region, the pressure drop was little influenced by the inlet fluid temperature (Tb,in). However, in the subcooled boiling region, the pressure drop increased rapidly with the increasing Tb,in. A higher G leads to a high pressure drop. In the SP region, the influence of p on the pressure drop is not obvious, and the pressure drop decreased with the increasing qe. The test data are used to evaluate the typical pressure drop correlation, and the results show that none of these correlations can predict the pressure drop well under the test conditions. Therefore, a new pressure drop correlation is proposed for subcooled water in a hypervapotron under high and non-uniform heat fluxes. The new correlation has a high prediction accuracy for the test data, and the mean relative error (MRE) and root mean square error (RMSE) are 0.72% and 4.33%, respectively. The test results have a reference value for the design of the water-cooling structure of the diverter.